FE modeling of concrete with strong discontinuities for 3D shear fractures and comparison with experimental results. (15th June 2021) - Sun, Yue; Roubin, Emmanuel; Shao, Jianfu; Colliat, Jean-Baptiste
Highlights: A new kinematics for embedded strong discontinuities is proposed. This kinematics includes a closure mechanism for mode II sliding opening. Heterogeneous materials are simulated with explicit heterogeneities. The added closure mechanism leads to some emergent hysteresis phenomena. Comparison between the experimental results shows good consistency. Abstract: In this paper, a new Enhanced Finite Element Method (E-FEM) model is proposed to describe 3D shear fractures of quasi-brittle materials such as concrete. Special attention is made to the failure behaviors in cyclic loadings as it is a common phenomenon in practical engineering. Within the framework of the E-FEM, the discontinuities are locally embedded in the finite elements. Here, two kinds of discontinuity enhancements are used in this model: weak discontinuities allow the model to represent heterogeneities in an unstructured mesh explicitly, and strong discontinuities enable the displacement jumps in finite elements to perform cracks and fractures. In this paper, our interest is focused on the shear sliding discontinuity (mode-II). The closure mechanism is also taken into concern, which simulates frictional sliding forward and backward between the lips of cracks. Then the performance of the proposed model is tested and analyzed by comparing it to experimental results. Certain limitations of the simulation are pointed out, and the corresponding solutions are addressed. Finally, the consistencies and differences between the simulation and the experimental results are discussed.